Effect of grain size on piezoelectric, ferroelectric and dielectric properties of PMN-PT ceramics. Issue 5 (1st April 2019) - Pramanik, R.; Sahukar, M.K.; Mohan, Y.; Praveenkumar, B.; Sangawar, S.R.; Arockiarajan, A.
Abstract: Grain size has significant effects on the electromechanical response of piezoceramics. Since the sintering temperature and holding duration affect the grain size and correspondingly their effective piezoelectric response, these issues should be appropriately addressed in order to properly design smart and intelligent systems. In this paper, PMN-PT piezoceramics with different grain sizes are synthesized by using conventional solid state processing and two-stage sintering method. Grain size effects on the hysteresis, fatigue and creep response are analyzed. Dielectric, ferroelectric and piezoelectric material properties of PMN-PT ceramics are investigated. The piezoelectric coefficient and remnant polarization exhibit diverse grain size effects depending on the sintering temperature and holding duration. The relative dielectric permittivity, piezoelectric coupling constant and dielectric constant show maximum values of 4104.2, 559 pC/N 562.291 pC/N and 0.705 for the microstructure with average grain size of 3.8 μm. The myriad effects of grain size on piezoelectric response are reported in details.